Metodologia estrangeira, prática brasileira? Análise das ações da plant-for-the-planet no Brasil para o ensino das mudanças climáticas - Araripe, Evelyn de Oliveira (Universidade Federal de São Carlos, 2020)
This dissertation aims to analyze in a critical way the potentialities and the gaps of the methodology of the German organization Plant-for-the-Planet in Brazil to teach climate change to Brazilian children and youngsters. Therefore, twenty-nine children, teenagers and youngsters who had already participated in some activities of the organization in the cities of Araranguá/SC, Mariana/MG and Salvador/BA were interviewed by survey and group interview. It was observed socio-economical aspects of the audience attended by the organization, their previous knowledge about climate change before participating in the activities organized by Plant-for-the-Planet (named Academies), and the learning acquired in an Academy. Among the results, it was noticed that most of the participants had learned about climate change in Science classes. Outside the school, they have learned about this topic mainly by television or at home by talking with their parents. Even after a Plant-for-the-Planet's Academy, where they had participated in a tree planting action, the participants had difficulties in naming tree species, and most tree species mentioned were fruit trees (association with food). The knowledge of the participants about climate change kept superficial after the Academy, but the life story of the young boy Felix Finkbeiner, founder of Plant-for-the-Planet, is memorized and inspiring for those children, teenagers and youngsters. Consequently, one conclusion is that the use of role models is a strong aid in teaching about climate change. And it is proposed that a role model closer to the participant’s realities and nationality will most likely have an even higher impact. Another proposal based on the data collected is to intensify the teaching about tree species at schools, using the agroforests in the proximity of the schools as an aid for continuous learning and to raise awareness on topics related to climate education.
Foreign methodology, brazilian practice? Analysis of plant-for-the-planet's actions in Brazil to teach climate change
Keywords: Mudanças climáticas; Educação ambiental crítica; Educação climática; Agrofloresta; Árvores; Climate change; Climate education; Critical environmental education; Trees; Agroforest; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO